2011
DOI: 10.1016/j.jtcvs.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve dysplasia syndrome: A unique form of left-sided heart disease

Abstract: Mitral valve dysplasia syndrome is a unique form of congenital heart disease with severe aortic stenosis but normal or enlarged left ventricle secondary to primary mitral valve disease. Increased left heart size and pulmonary vein Doppler patterns are predictive of postnatal outcome. Despite the presence of a dilated left ventricle, postnatal management with staged single ventricle palliation may be the most effective strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…487,488 Incompetence of the mitral valve is typically attributable to a mitral valve arcade with combined stenosis and insufficiency. Severe mitral regurgitation leads to left atrial dilatation with a restrictive or intact atrial septum.…”
Section: Mitral Valve Dysplasia Syndrome With Mitral Regurgitation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…487,488 Incompetence of the mitral valve is typically attributable to a mitral valve arcade with combined stenosis and insufficiency. Severe mitral regurgitation leads to left atrial dilatation with a restrictive or intact atrial septum.…”
Section: Mitral Valve Dysplasia Syndrome With Mitral Regurgitation Anmentioning
confidence: 99%
“…Fetal cardiac intervention may be considered to open the aortic valve and to promote forward flow 487 ; however, aortic regurgitation after the procedure may complicate the physiology. Opening of the atrial septum with the goal of decompressing the left atrium and improving filling of the right side has also been proposed 488 and may be considered. Left ventricular dysfunction and mitral valve disease may still prevent the use of the left ventricle for a biventricular repair, and a single-ventricle strategy may still be necessary after birth.…”
Section: Mitral Valve Dysplasia Syndrome With Mitral Regurgitation Anmentioning
confidence: 99%
“…Critical AS, massive mitral regurgitation (MR), giant left atrium (LA), and fetal hydrops. 17,18 a. These form a unique and challenging subgroup of patients who have been described as such only recently.…”
Section: Relevant Anatomy and Preprocedures Planningmentioning
confidence: 99%
“…17,18 A recent published series showed that this condition is commonly associated with either fetal loss or prematurity and carries a somber prognosis no matter what is performed in the prenatal or postnatal periods. 17 Perhaps in utero ASD creation or enlargement should have been given the same importance as aortic valve dilation.…”
Section: Fetal Cardiac Interventionsmentioning
confidence: 99%
“…Der Erfolg der Dilatation lässt sich in der Regel direkt nach dem Eingriff sonografi sch beurteilen, wenn der antegrade Fluss in der aszendierenden Aorta deutlich zunimmt, eine passagere Aortenregurgitation sichtbar wird und sich der zuvor prall dilatierte kaum kontraktile besser kontrahiert und "entspannt" erscheint. beschriebenen abnormalen Blutfl ussgeschwindigkeitsprofi len in den zudem meist an ihren Einmündungen dilatierten Lungenvenen eine Linksherz/Rechtsherz-Flächen-Ratio > 1,5 [ 16 ] sowie das Auftreten eines progredienten Hydrops fetalis [ 49 ] . In letzterer Situation gilt es, den Eingriff als lebensrettende Maß-nahme durchzuführen [ 17 , 50 ] [ 3 ] .…”
Section: Entwicklung Fetaler Katheterinterventionenunclassified